(untitled) (Shahroud Journal of Medical Sciences, 2020)
Background: Malnutrition is common in hemodialysis patients and it must be controlled quickly. This study aimed to investigate the effect of zinc sulfate on malnutrition in dialysis patients. Methods: This study was a randomized controlled trial on 84 hemodialysis patients referred to Imam Hossain Hospital in Shahroud (northeastern of Iran). Patients were randomly divided into two case and control groups. For the intervention group, one tablet of zinc sulfate 220 mg was administered daily for 8 weeks. Both groups were subjected to standard dialysis three times in the week and all patients were assessed for malnutrition using a standard questionnaire, lab tests, and necessary examinations in the first stage, one month and two months after the treatment. Results: Of 84 patients, 39 cases (46.4%) were female and rest was male. The mean age of the patients was 59.1±27.2 years. The mean total duration of dialysis was 2.9±2.3 years. The severity and extent of malnutrition at the beginning and one month after the study did not differ between the two groups, but after the second month, there was a significant decrease of malnutrition in the intervention group (Pvalue=0.015). Also, malnutrition variables were significantly associated with BMI less than 18 kg/m2 (Pvalue<0.039), and serum creatinine less than 3 mg/dl (Pvalue<0.011) and hemoglobin less than 11 g/dl (Pvalue<0.001), Conclusions: The results of this study showed that zinc sulfate consumption for at least 2 months could significantly reduce the severity of malnutrition in hemodialysis patients. Keywords: Malnutrition, Zinc sulfate, Hemodialysis.